2018
DOI: 10.1186/s12933-018-0737-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between sodium glucose co-transporter 2 inhibitors and a reduced risk of heart failure in patients with type 2 diabetes mellitus: a real-world nationwide population-based cohort study

Abstract: BackgroundRecently, two large randomized controlled trials which only included patients with underlying cardiovascular disease (CVD) or patients at high risk for CVD showed that two sodium glucose co-transporter 2 inhibitors (SGLT-2is) significantly reduced hospitalization for heart failure (hHF), with an early separation in the survival curves for hHF. There were concerns whether SGLT-2i use could protect hHF in patients without CVD and how soon SGLT-2i-treated patients show a lower risk of hHF. Thus, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
2
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 35 publications
5
55
2
4
Order By: Relevance
“…The risk of HF was also examined by comparison with results from previous studies. 15,16,24 Lastly, we…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The risk of HF was also examined by comparison with results from previous studies. 15,16,24 Lastly, we…”
Section: Discussionmentioning
confidence: 90%
“…Our results on the risks of MI and HF support previous findings from observational studies, which showed that the risk of MI or HF for patients given DPP‐4Is was significantly higher than for those taking BGs but lower than those taking SUs. Ou et al showed that DPP‐4Is were associated with increased risk of MI and HF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations